Cytotoxicity of Silver Nanoparticles on Human Gingival Epithelial Cells: An In Vitro Study - Taleghani, Feriyal; Yaraii, Roya; Sadeghi, Rokhsareh; Haghgoo, Roza; Rezvani, Mohammad Bagher (Journal of Dental School, 2019)
Objective: Nanosilver has numerous applications in medicine due to its potent antibacterial activity. However, data regarding the bio-safety of its effective concentrations is scarce. This study aims to assess the toxicity of silver nanoparticles on human gingival epithelial cells under in-vitro conditions. Methods: This in vitro study evaluated the toxic effects of filtered and unfiltered nanosilver solution on human gingival epithelial cells obtained from the Pasteur Institute of Iran using the methylthiazol tetrazolium bromide (MTT) assay (mitochondrial function)and membrane leakage of lactate dehydrogenase (LDH) at 24, 48 and 72h time points. The concentrations of silver nanoparticle solution used were 0.05, 0.1, 0.2, 0.5, 1, 2, 5, 10, 20 and 50µg/ml. Results: The MTT assay showed that nanosilver solution at high concentrations (20 and 50µg/ml) significantly decreased the viability of cells at all time points. The lower non-fatal concentrations at 24 and 48h were capable of causing cell death or significantly inhibit cell growth at 72h. The LDH assay demonstrated that death of epithelial cells only occurs at high concentrations of nanosilver (20 and 50µg) and no significant toxicity was seen at lower concentrations. Conclusion: Based on the results, silver nanoparticles have toxic effects on human gingival epithelial cells and this effect is time and dose-dependent.